Laser hardening of 420 martensitic stainless steel and 2205 duplex stainless steel - Koh, Swee Sheng (2019)
Laser surface treatment has the ability to alter the mechanical and chemical properties of material such as steel. In this study, AISI grade 420 Martensitic Stainless Steel (MSS) and 2205 Duplex Stainless Steel (DSS) are treated with IPG Photonics DLR-1500-Y14 Ytterbium-Doped Fiber laser. Each of the materials are treated at 1500W, 1200W, 900W and 600W to study the different impacts of the varying laser power. As such, the author prepared samples of the treated materials through the standard preparation techniques. Further which, the samples are examined via a series of different microscopes and tested with the Vickers Hardness Test Machine to express the characteristics found in the different configuration of each material. The study showcase the different effects that are present such as the influence of overlapping laser track in the material, absorptivity of polished and non-polished surfaces, and microstructure in material hardness. This includes data on the depth of the treatment and hardness profile of each configuration of the material. Thereafter, results show that non-polished surfaces have the edge in absorptivity which benefitted the material in terms of hardness enhancement. Per se, the condition of the surface translates to the surfaces’ receptivity to the energy provided in the treatment which conjugates greatly to the success of the treatment. If successful, it can enhance the material’s hardness beneath the treated surface by a few fold of its original hardness. In this configuration, it can enhance by up to 2.7 times for MSS and 0.30 times for DSS of their original hardness of 175HV and 250HV respectively. Unlike conventional heat treatment methods where greater volume of the material is enhanced, the laser localizes the treatment and hardens a few mm of the material beneath the treated surface. Given the unique compositions of each material and its hardness, they are found to be relevant in industrial applications such as dental and surgical instruments for the MSS, and marine and transport for DSS.